1979
DOI: 10.1073/pnas.76.6.2974
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of somatostatin from pigeon pancreas.

Abstract: Most of the somatostatin-like activity from pigeon pancreas was found to correspond to a small species with an apparent molecular weight of 1500-2500. This species was isolated under conditions minimizing intermolecular interactions and protease activities. The isolated product was characterized by two somatostatin radioimmunoassays, a bioassay, endgroup determination, and amino acid analysis. The structure of the isolated compound was determined to be H-Ala-Glycyclo-(Cys-Lys-Asn-Phe-Phe-Trp-Lys-Thr-Phe-Thr-Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
38
0
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 20 publications
0
38
0
1
Order By: Relevance
“…5 mg of pancreatic somatostatin was isolated from islets obtained from 400 lb of fish (-100-150 fish). On the basis of previously published estimates (11)(12)(13) fish somatostatins are bigger. Furthermore, the sequence of fish insulins differs from mammalian insulin in up to 50% of the amino acids, yet they maintain considerable biological activity in mammalian systems (28 A small amount of somatostatin comigrated with the tetradecapeptide.…”
Section: Isolation Of Immunoreactive Pancreatic Somatostatinmentioning
confidence: 99%
See 3 more Smart Citations
“…5 mg of pancreatic somatostatin was isolated from islets obtained from 400 lb of fish (-100-150 fish). On the basis of previously published estimates (11)(12)(13) fish somatostatins are bigger. Furthermore, the sequence of fish insulins differs from mammalian insulin in up to 50% of the amino acids, yet they maintain considerable biological activity in mammalian systems (28 A small amount of somatostatin comigrated with the tetradecapeptide.…”
Section: Isolation Of Immunoreactive Pancreatic Somatostatinmentioning
confidence: 99%
“…It was noted that both big and small somatostatin from crude pancreas and stomach extracts displaced tracer in a manner parallel to that of synthetic somatostatin, indicating that the gastric and pancreatic somatostatin-like substances were immunologically indistinguishable from the somatostatin tetradecapeptide. Spiess et al (13) found most of the somatostatin-like activity of pigeon pancreas was 1,500-2,500 mol wt, but a small amount of material 11,000-12,500 mol wt was also found. Noe et al (29) incubated slices of anglerfish islets for several hours, then chromatographed acid extracts on Bio-Gel P-10.…”
Section: Isolation Of Immunoreactive Pancreatic Somatostatinmentioning
confidence: 99%
See 2 more Smart Citations
“…Pradayrol et aL (8) determined the amino acid sequence of a 28-residue somatostatin precursor from porcine intestine, and Schally et aL (9) and Esch et aL (10) have determined the sequence of a 28-residue peptide from bovine and ovine hypothalami, respectively. These precursors to somatostatin have amino-terminal extensions and share the common 14-amino acid sequence found in ovine (1), porcine (11), pigeon (12), and angler fish (13) somatostatin. Recently the amino acid sequence of a somatostatin isolated from channel catfish was reported (14).…”
mentioning
confidence: 99%